Determinanty struktury organizacyjnej na przykładzie dużych polskich przedsiębiorstw produkcyjnych - Zakrzewska-Bielawska, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The organizational structure is the result of many various factors, which run in different direction and with different strength. Among these factors one can distinguish: environment, size and the age of the organization, degree of the diversification of the production, technology, people, organizational culture and strategy. These factors strengthen or neutralize their structure features in dependence on situational conditions of the enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 99-108